Exploring AI Gliglish to Enhance English Speaking Skills among Secondary School Students in Thailand: A Classroom Action Research Study on Confidence and Proficiency - Radhiyya, Fasya Putri; Nasution, Dewi Kesuma; Ginting, Pirman (Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking proficiency is a crucial skill for global communication, yet many Thai secondary school students struggle with fluency and confidence due to limited exposure to authentic language use and traditional grammar-focused instruction. Existing research on AI-assisted language learning highlights its potential, but studies on AI Gliglish in Thai classrooms remain scarce. AI Gliglish is an AI-powered English learning platform designed to provide real-time speech assessment, feedback, and interactive conversation practice. This study investigates the effectiveness of AI Gliglish in enhancing students’ speaking proficiency and confidence using a Classroom Action Research approach. Data were collected from 30 Grade 7 students at Muslim Satun Wittaya School, Thailand, through pre-test, post-test, interviews, and classroom observations. Findings indicate a 19.25% improvement in speaking scores, increased student participation, and reduced speaking anxiety. The Paired Sample T-Test (Sig. 0.001 0.05) confirms a statistically significant impact. These results suggest that AI Gliglish effectively enhances speaking skills, supporting its integration into English language education to foster engagement, fluency, and confidence.